Chronicle of the American War of 1941 - Masterman, Howard W.
Photocopy of typescript titled, "Chronicle of the American War of 1941" written by Masterman while serving on board the U.S.S. Wright (aircraft tender). Relates chiefly to the attack on Pearl Harbor, December 7, 1941, and campaigns in the Pacific Ocean during December 1941. Includes a description of the naval base at Pearl Harbor written by Masterman while on the U.S.S. Wright which arrived there the day after the attack.
Photocopy of typescript.
Naval officer.
Forms part of: Naval Historical Foundation collection.
Keywords: Wright (Aircraft tender); Navy-yards and naval stations -- Hawaii -- Pearl Harbor; Pearl Harbor (Hawaii), Attack on, 1941.; World War, 1939-1945 -- Campaigns -- Pacific Ocean; World War, 1939-1945 -- Naval operations, American; Naval officers